Estimation of smoke plume height from early burning via simulation - Panuphan Limthavorn (2018)
Early burning is one of forest fire management techniques which decreases surface fuel accumulated on the floor in dry dipterocarp forest to abate forest fire severity. Early burning may cause air pollution to local people from smoke dispersion. This study is thus focused on the simulation of plume height by Fire Dynamics Simulator (FDS) by using weather data between 13 th -17 th January 2013 because this period have enough fuel accumulated for the fuel management and also before wildfire season. This study use meteorological data in from Weather Research and Forecasting (WRF) model. The sample area was separated into 5 plots depending on altitude (2, 2, and 1 plots were located at 400, 500, and 600 m above mean sea level, respectively).The results from FDS shown that the smoke plumes at the height 400 m above mean sea level is rising about 100 meters, the smoke plumes at the height 500 m above mean sea level is rising about 250 and 480 meters and the smoke plumes at the height 600 m above mean sea level is rising 400 meters. From the results shown that the smoke plumes never rise above 1200 meters above mean sea level that is the level of planetary boundary layer height of that day. It is clear that the smoke plume height is depend on heat released rate per unit area (HRRPUA) and environmental lapse rate. © (2014) Trans Tech Publications, Switzerland.